Function and Dysfunction of Complement Factor H During Formation of Lipid-Rich Deposits - Meri, Seppo; Haapasalo, Karita (Frontiers in Immunology, 2020)
Complement-mediated inflammation or dysregulation in lipid metabolism are associated with the pathogenesis of several diseases. These include age-related macular degeneration (AMD), C3 glomerulonephritis (C3GN), Dense Deposit Disease (DDD), atherosclerosis and Alzheimer’s disease (AD). In all these diseases formation of characteristic lipid-rich deposits is evident. Here we will discuss molecular mechanisms whereby dysfunction of complement, and especially of its key regulator factor H, could be involved in lipid accumulation and related inflammation. The genetic associations to factor H polymorphisms, the role of factor H in the resolution of inflammation in lipid-rich deposits, modification of macrophage functions and complement-mediated clearance of apoptotic and damaged cells indicate that the function of factor H is crucial in limiting inflammation in these diseases.